(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The results of chemical analysis showed that the main components of brine from lakes Borsakelmas and Karaumbet are sodium, magnesium cations, chlorine and sulfate anions. Calcium and iron are practically absent. The salt content in brine ranges from 30 to 42%. The chemical composition of brine from the Borsakelmas deposit is noticeably different from the composition of brine from the Karaumbet deposit in that it contains more sodium and chlorine ions. And the brine of the Karaumbet deposit has a higher content of magnesium and sulfate ions. It has been shown that the brine of the Karaumbet deposit contains more magnesium salts and less sodium salts, which is in good agreement with reference data on the study of solubility in the systems Na+, Mg2+//SO42-, CI- – H2O. The total salt content of Karaumbet brine is approximately 1.2 times higher than the Borsakelmas brine, but at the same time the NaCl content is 4-5% lower, which indicates that a significant part of the NaCl from the Karaumbet brine has already been separated into sediment and this process continues.